Book review: Islam translated: literature, conversion, and the Arabic cosmopolis of South and Southeast Asia by Ronit Ricci - Ahmad, Siti Nuraishah (Universiti Sains Malaysia, 2017)
The coming of Islam to South Asia and Southeast Asia has long held the interest of scholars of religion, history and culture around the world. There is an impressive body of work on the Islamisation of these regions, studying its routes and the roles played by traders, missionaries, Sufi brotherhoods and diplomatic emissaries. Lesser known, perhaps, is the role of literary activity such as composing, translating and the public reading of texts, in the spread of Islam in these regions. The award-winning1 Islam Translated: Literature, Conversion, and the Arabic Cosmopolis of South and Southeast Asia by Ronit Ricci sets out to investigate how literary texts, their production and translation contributed to Islamisation in South India, Java and the Malay world. The writing of literature and their translation into vernacular languages, Ricci proposes, are intertwined with the conversion to Islam of people and cultures in these regions. The text at the centre of Ricci's study is the Book of One Thousand Questions, which was translated into multiple languages from the original Arabic, including Tamil, Javanese and Malay. To understand the significance of this text and its correlation with the themes explored in Ricci's book, it is necessary to provide a brief summary of the Book of One Thousand Questions and how it came to South and Southeast Asia. .......